Transformation in times of climate change: what makes a fisher diversify livelihoods? - Salgueiro-Otero, Diego; Barnes, Michele L.; Ojea, Elena (Frontiers in Marine Science, 2022)
Despite the importance of livelihood diversification as a transformation strategy in small-scale fisheries facing climate change, empirical evidence on this complex phenomenon is scarce. This work aims to shed light on factors that help to explain the transformative behavior of small-scale fishers when faced with climate change impacts. Using primary survey data from 404 small-scale fishers across 9 communities in Galicia, NW Spain, we examined how different aspects of fishers’ adaptive capacities relate to their stated decisions to engage in livelihood diversification when faced with hypothetical climate change scenarios. The results of our multinomial multilevel mixed-effect logit model show that flexibility (current income diversification level and diversity of target fishery resources) has a strong, positive relationship with livelihood diversification responses. In contrast, learning, social organization, and competing concerns played a complex role. Specifically, we found that social-ecological system knowledge, communication with different fishing groups (bridging communication), trust in institutional actors, and gender (female) were positively related to livelihood diversification when faced with climate impacts. Fishing experience, communication within fishing groups (bonding communication), and trust in other fishing groups (bridging trust) were negatively related to diversification. Our results provide new empirical evidence on the factors associated with fisher’s decisions to engage in livelihood diversification when faced with climate impacts on fishery resources, lending critical insight for climate adaptation programs and policies.